2015
DOI: 10.1038/onc.2015.65
|View full text |Cite
|
Sign up to set email alerts
|

LINE-1 induces hTERT and ensures telomere maintenance in tumour cell lines

Abstract: A hallmark of cancer cells is an activated telomere maintenance mechanism, which allows prolonged survival of the malignant cells. In more than 80% of tumours, telomeres are elongated by the enzyme telomerase, which adds de novo telomere repeats to the ends of chromosomes. Cancer cells are also characterized by expression of active LINE-1 elements (L1s, long interspersed nuclear elements-1). L1 elements are abundant retrotransposons in the eukaryotic genome that are primarily known for facilitating aberrant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 81 publications
4
51
0
1
Order By: Relevance
“…Autophagy plays crucial roles in cancer, recent study revealed that enhanced autophagic activity was detected in ovarian cancer stem cells, and inhibition of autophagy reduced chemoresistance and self-renewal [23]. Activated telomere maintenance mechanism allows prolonged survival of the cells, which considered as a hallmark of cancer cells [24]. Therefore, differentially expressed genes that enriched in these biological processes and pathways might be important contributors of the enhanced malignancy of LSCC stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays crucial roles in cancer, recent study revealed that enhanced autophagic activity was detected in ovarian cancer stem cells, and inhibition of autophagy reduced chemoresistance and self-renewal [23]. Activated telomere maintenance mechanism allows prolonged survival of the cells, which considered as a hallmark of cancer cells [24]. Therefore, differentially expressed genes that enriched in these biological processes and pathways might be important contributors of the enhanced malignancy of LSCC stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, full-length LINE-1 elements (L1s, long interspersed nuclear elements-1) are repeat-rich intronic or intergenic (junk) sequences, and are transcribed as euchromatin RNAs (ecRNAs) that may play a role in chromosome structure and regulation by promoting a more open chromatin state [109]. L1s become inactivated early in development, while recent evidence indicates they can be activated in cancer [110,111], as well as neurodegeneration (reviewed in [112]) and during development in the brain (reviewed in [113,114]).…”
Section: Epigenetic Regulation Of Tmmsmentioning
confidence: 99%
“…Importantly, this abundant L1 RNA signal is from the numerous 5′ truncated L1s, distinct from the small number of full-length L1 elements capable of retrotransposition. Full-length L1s are inactivated early in development, although recent evidence indicates they can be activated in cancer [40,41], neurodegeneration (reviewed in: [42]) and during development in the mammalian brain ([43,44] reviewed in: [45,46]). However, this likely represents a separate phenomenon from the L1-rich Cot-1 ecRNA prevalent in all cells.…”
Section: Repeat-rich “Cot-1 Rna” As An Abundant Stable Component Of mentioning
confidence: 99%